Rolasan : Program to Improve The Quality of Memorization Santri Hafizhat Al-Qur’an - Hanifah Hikmawati; Zuhriana Widya Rahayu Ning Tyas; Luluk Muasomah; Umi Choiriyah (Attanwir : Jurnal Keislaman dan Pendidikan, 2025)
This study aims to reveal the  rolasan   as a program to improve the quality of santri s' memorization. To achieve good quality of memorization of the Qur'an, good management is needed to manage from planning, organizing, implementing, and supervising in order to achieve the goals made. Research This use approach qualitative with method descriptive . The data in study qualitative This in the form of primary and secondary data obtained with method interviews , observations and documentation . The data that has been collected Then analyzed with method analysis qualitative descriptive . Research results This show quality memorizing the Qur'an by santri s at the pondok pesantren Baitul Akbar is growing maximum because in the cottage pondok pesantren the more prioritize murojaah than adding​ memorization. Besides that is , rolasan program management  can increase quality memorization santri  that is with how the memorizers of the Qur'an interact with each other listen and pay attention a assembly in a way alternate read volume by listening​ without mushaf Al-Qur’an by his friend .